The Kitt Peak Electron Multiplying CCD demonstrator. Issue 1 (17th February 2019) - Coughlin, Michael W; Dekany, Richard G; Duev, Dmitry A; Feeney, Michael; Kulkarni, S R; Riddle, Reed; Ahumada, Tomás; Burdge, Kevin; Dugas, Alison M; Fremling, Christoffer U; Hallinan, Gregg; Prince, Thomas A; et al.
Abstract: The Kitt Peak Electron Multiplying CCD (EMCCD) demonstrator is a new instrument that has been developed for use at the Kitt Peak National Observatory's 84-inch telescope. The EMCCD enables single-band optical imaging in the Sloan g and r bands and Johnson UVRI filters. The EMCCD is chosen for its sub-electron effective read noise using large multiplicative gains. With these systems, frame rates of greater than 1 Hz are possible. The field of view is 4.4 × 4.4 arcmin 2 and the pixel size is 0.259 arcsec. This camera, coupled with a fully roboticized telescope, is ideal for follow-up of short period, white dwarf binary candidates, as well as short duration transient and periodic sources identified by large field-of-view all-sky surveys such as the Zwicky Transient Facility.